Enhancing the outcomes of mergers and acquisitions - Miguel, João Carlos Pereira (2018)
This work is focused on the variables that influence the outcomes of mergers and acquisitions, with emphasis on the ones that can be molded and improved. How companies desiring to perform mergers or acquisitions can learn from past mistakes, adopt better strategies and make wiser decisions to enhance the outcomes of their mergers and acquisitions. By improving the success of such deals, greater economic development can be achieved; mergers and acquisitions can act as powerful strategic movements that rehabilitate entire sectors. The literature review is focused on the importance of strategic fit and complementarity; culture; communication; speed of integration and human resources management. The research questions were focused on how to improve synergy estimations; the importance of culture, how to address it and improve cultural evaluation; how to extract the value of deals between companies with cultural incompatibilities; the viability of adopting a less standardized approach that tries to seek more and deeper synergetic sources of value and how to prepare companies for the realization of mergers and acquisitions with special prominence on transformational deals.